SINTESIS DAN KARAKTERISASI MAGNETIT (Fe3O4) SERTA APLIKASINYA SEBAGAI ADSORBEN METHYLENE BLUE - Retno Agnestisia (Jurnal Sains dan Terapan Kimia, 2017)
Synthesis, characterization and adsorption study of magnetite have beenconducted. Magnetite was synthesized by coprecipitation method. The characterizations of magnetite were carried out with spectroscopy FTIR (Fourier Transform Infrared) and XRD (X-ray diffraction). The adsorption study was conducted using a batch system with the studied adsorption study including optimum pH, optimum contact time and adsorption equilibrium. The results showed that coprecipitation method has succeeded to form magnetite that has magnetism properties. Magnetite can adsorbed methylene blue from aqueous phase, with the maximum adsorption at pH 5 and contact time of 90 minutes. Adsorption of methylene blue by magnetite follows the adsorption pattern of the Langmuir isotherm with the adsorption energy of 25.59 kJ/mol and adsorption capacity of 43.86 mg/g. The results of magnetite synthesis can accelerate the process of separating the adsorbent particles in a methylene blue solution using an external magnetic field.Keywords : magnetite, coprecipitation, adsorption, and methylene blue.